Analyzing the Branding of Kendal Regency's Branding as an Industrial City and its Relationship to Investor Perception - Wulan Aristriana; Ahmad Anif Syaifudin; Miandhani Denniz Yuniar (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to analyze the branding design of Kendal Regency as an industrial city and its relationship with investor perceptions and the region's investment attractiveness. The approach used is qualitative descriptive-analytical with data collection techniques through in depth interviews, observations, and documentation studies of 15 informants consisting of local government, industrial area managers, and investors. The results of the study indicate that Kendal's identity as an industrial area has been factually formed through the existence of industrial areas, infrastructure support, and strategic locations, but has not been integrated into a consistent branding narrative. This study produces a regional branding model consisting of three main components, namely (1) industrial area identity as a foundation that reflects the economic potential and character of the region, (2) strategic communication through promotional media, digital platforms, and business networks, and (3) institutional collaboration between local government and industrial area managers. The integration of these three components shapes investor perceptions that influence investment decisions. Theoretically, this study enriches the study of place branding by integrating the perspective of development communication in the context of district-level industrial areas. Practically, the results of the study provide recommendations for local governments to design integrated, consistent, and value-based branding strategies to increase investment attractiveness in a sustainable manner.